Students' Perception Of Machining Workshop Facilities And K3 Knowledge Towards Learning Outcomes In The Subject Of Lathe Machining Engineering In Grade 11 Of SMK Negeri 1 Sumatera Barat - Ahmad Rifai Sihombing; Arwizet K; Rifelino Rifelino; Primawati Primawati (Jurnal Vokasi Mekanika (VoMek), 2025)
Vocational schools are a strategic forum to introduce and build students' awareness of the importance of behaviors that support Occupational Health and Safety (K3). Based on the results of pre-observation at SMK Negeri 1 West Sumatra, it was found that several problems were quite significant related to learning outcomes and students' knowledge about Occupational Health and Safety (K3) in the Lathe Machining Engineering Subject. Inadequate workshop facilities result in students not understanding and not utilizing K3 equipment. This problem is the author's material to conduct research to measure Students' Perception of Machining Workshop Facilities and Students' K3 Knowledge of Student Learning Outcomes which is carried out by descriptive analysis methods. This study analyzed two independent variables and one dependent variable. Variables Workshop facilities, variables K3 Knowledge and Learning Outcomes as variables Y. The purpose of this study is to show that the percentage results obtained from each variable can describe how students' perception of the K3 Machining and Knowledge Workshop Facilities and Learning Outcomes are. The results of the study show that the value of the variable (Workshop Facility) has a perception at a low level, namely 7 (35%) students, the variable (K3 Knowledge) can illustrate that students' perception of K3 Knowledge is very high where as many as 7 (35%) students have this perception This illustrates that students' understanding of K3 Knowledge is very good. Furthermore, the Y variable (Learning Outcomes) shows a high percentage value it can concluded that most students have a good understanding of K3 Knowledge.